Aplikasi Kesehatan Ibu Hamil Berbasis Android - Ardianto Pambudi; Nurchim; Agustina Srirahayu (Jurnal Infokes, 2020)
In Indonesia, the mortality rate for pregnant women is still high. One of the contributing factors is the lack of knowledge and awareness of communication between pregnant women and midwives in the process of antenatal care, resulting in a delay in recognizing the danger signs of pregnancy. The purpose of this study is to provide a pregnant mother's health application that can be run on an android system. Android as a smartphone operating system, supports the development of new application ideas and innovations to add system functionality. The stages of making the application include (1) analyzing user needs by observing the Independent Practice Midwife in the Polokarto Sukoharo area, Central Java. Next, (2) design a system consisting of two users, including midwives and pregnant women. Finally, (3) the implementation of making a system design in the form of an android application. This Maternal Health Application has a feature that pregnant women can communicate with midwives directly to submit complaints, examination results, information about pregnancy and the calculation of Estimated Birth Days (HPL). Thus, it is hoped that this application can be used as a digital health service that facilitates access to information and public health services, especially those related to pregnancy.